89.9k views
4 votes
Solve the equation. 12x – 15 = 3(2x +3)

1 Answer

4 votes

Answer:

x = 4

Explanation:

Solve for x:

12 x - 15 = 3 (2 x + 3)

Hint: | Write the linear polynomial on the left hand side in standard form.

Expand out terms of the right hand side:

12 x - 15 = 6 x + 9

Hint: | Move terms with x to the left hand side.

Subtract 6 x from both sides:

(12 x - 6 x) - 15 = (6 x - 6 x) + 9

Hint: | Combine like terms in 12 x - 6 x.

12 x - 6 x = 6 x:

6 x - 15 = (6 x - 6 x) + 9

Hint: | Look for the difference of two identical terms.

6 x - 6 x = 0:

6 x - 15 = 9

Hint: | Isolate terms with x to the left hand side.

Add 15 to both sides:

6 x + (15 - 15) = 15 + 9

Hint: | Look for the difference of two identical terms.

15 - 15 = 0:

6 x = 9 + 15

Hint: | Evaluate 9 + 15.

9 + 15 = 24:

6 x = 24

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides of 6 x = 24 by 6:

(6 x)/6 = 24/6

Hint: | Any nonzero number divided by itself is one.

6/6 = 1:

x = 24/6

Hint: | Reduce 24/6 to lowest terms. Start by finding the GCD of 24 and 6.

The gcd of 24 and 6 is 6, so 24/6 = (6×4)/(6×1) = 6/6×4 = 4:

Answer: x = 4

User Siphalor
by
5.6k points